Bayaning 3rd world (Viva Video, 2001)
A witty and unpredictable film that broadens the discussion on the life of Jose Rizal, with "interviews" with the key players in the last moments of his life: his mother, brother and sisters, wife/mistress, Jesuit clerics, his military defender and Rizal himself.